Synthesis and evaluation of antimitotic activity of new tetralone acid analogues of podophyllotoxin - Shivakumar, Santhekasalagere Basavaiah; Basavaraju, Yeriyur Basavaiah; Umesha, Basavaiah; Krishna, Mudeenahally Hucchegowda; Mallesha, Ningegowda (European Journal of Chemistry, 2014)
The new tetralone acids (7a-e) were synthesized as analogues of podophyllotoxin. They were prepared by replacing 3,4,5-trimethoxyphenyl ring with cyclohexyl group in podophyllotoxin and 1,3-methylene dioxy ring with methoxy, hydrogen, methyl, thiomethyl, and fluorine atoms. The analogues of podophyllotoxin were synthesized using Gensler’s method with some changes in reagents and experimental procedure. The structures of the synthesized compounds were confirmed by IR, 1H NMR, 13C NMR, mass spectra and elemental analysis data. The synthesized tetralones acids were screened for their antimitotic activity. It is noteworthy that compound 7b possessed excellent antimitotic activity, 7c and 7e showed considerable activity and remaining 7a and 7d possessed low activity.